[OP.7C.10] IN PATIENTS WITH SUSPECTED CORONARY ARTERY DISEASE DICHOTOMIZED AORTIC PULSE WAVE VELOCITY IS DISCRIMINATIVE IN WOMEN BUT NOT IN MEN IN SURVIVAL ANALYSIS. (September 2017) - Mayer, C.; Hametner, B.; Parragh, S.; Whitelegg, K.; Weber, T.; Wassertheurer, S.
Abstract : Objective: Evidence for differences in aortic pulse wave velocity (PWV) between females and males depending on age has been reported previously. Nevertheless, there is a lack of studies covering the gender-specific influences when using PWV for survival analysis. Thus, the aim of this study is to investigate the interaction of sex and aortic PWV in a high risk cohort. Design and method: At the hospital in Wels-Grieskirchen (Austria) 928 patients with suspected CAD underwent coronary angiography. Catheter pullback was used to measure aortic PWV. Patients were grouped according to sex, aoPWV <= or > 10 m/s and all four combinations thereof. To minimize the influence of blood pressure (BP), PWV was corrected for invasive BP as recommended in the paper on normal and reference PWV values published on behalf of the European Society of Cardiology. A combination of myocardial infarction, death, stroke and cardiovascular revascularization served as primary endpoint. Kaplan-Meier curves, logrank test and hazard ratios were used for survival analysis. Results: In total, 604 male (61 (10 SD) years) and 324 female (65 (11 SD) years) were included. During a median follow-up of 1576 days, 215 patients suffered from an event. Kaplan-Meier curves are displayed in the figure. The hazard ratio between female and male patients with suspected CAD is 1.77 (95% CI = [1.35, 2.32], logrank: p = 0.0001) and between low and high aortic PWV 1.66 (95% CI = [1.23 to 2.24], logrank: p = 0.0002). Logrank test revealed significant differences (p < 0.0001) for the combined analysis for sex and PWV, but hazard ratios remained just significant for women with an aortic PWV < = 10 m/s, even though age differences are similar for both sexes (see Table). Results for corrected PWV were confirmatory. Conclusions: Dichotomized aortic PWV is discriminative in women in survival analysis in patients with suspected CAD, but not in men, in a high risk cohort. These findings were confirmed after adjustment for BP and underpin an interaction between arterial stiffness and sex. Continuous risk stratification in relation to age might be more beneficial. Figure. No caption available.